2013
DOI: 10.4103/2231-0746.110074
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided drainage of submasseteric space abscesses

Abstract: Background and Objectives:The objective of this study was to evaluate the usefulness of ultrasound guided surgical drainage in submasseteric space abscess of odontogenic origin without incision.Materials and Methods:Eleven patients (4 males and 7 females) aged 18 to 36 years were included in this study. Each patient had clinically and radiologically diagnosed submasseteric space abscesses of odontogenic origin. All the patients underwent ultrasound guided drainage by using 5.7 MHz B-mode, gray scale, ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Analysis with SPSS software found that USG precisely distinguished 84% of all included fascial spaces and 100% of included superficial spaces. These results were in near approximation to previous studies[ 4 , 5 , 18 , 19 ]. One previous study showed a significant association between histological findings and ultrasonography of oral maxillofacial swelling[ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…Analysis with SPSS software found that USG precisely distinguished 84% of all included fascial spaces and 100% of included superficial spaces. These results were in near approximation to previous studies[ 4 , 5 , 18 , 19 ]. One previous study showed a significant association between histological findings and ultrasonography of oral maxillofacial swelling[ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…Yeow et al also showed a case of deep neck abscesses in the parotid gland and retropharyngeal space (5,6). Al-Belasy and Gudi et al reported cases of puncture drainage in the masseter space (7,8). For the submandibular space, parapharyngeal space, and peritonsillar space, B-guided puncture drainage has also been shown to be an effective option (9)(10)(11)(12).…”
Section: Original Articlementioning
confidence: 99%
“…Fascial coverage of the masseter muscle and parotid gland is perfectly described by Hînganu et al 32 Masseteric and parotid fascias (also used a collective term for describing both fascias -'parotideomasseteric fascia' 2,33 [synonyms: parotideomasseteric fascia 9 , parotid-masseteric fascia 34 ]) present distinctive structures on ultrasound images. During US they are visualized as very thin hyperechoic linear structure which covers lateral surface of the masseter muscle and parotid.…”
Section: Discussionmentioning
confidence: 96%